Pengaruh Penerapan Model Problem Based Learning Terhadap Kemampuan Komunikasi Matematis dalam Pembelajaran Matematika SMPN 1 Lubuk Alung - Oktaviani, Dian (RC-INSTITUT, 2019)
Mathematics communication skill are abilities that are very important in learning mathematics that must be owned by students. But the mathematical communication skill in mathematics learning in class eight of junior high school 1 Lubuk Alung are still low. The solution is to apply the Problem Based Learning (PBL) model. This study to see the differences in mathematical communication skill of students who learn to use the Problem Based Learning model with students who learn to use conventional learning models. This study uses a quasi experimental design Randomize Control Group Only . The sampling technique was Simple Random Sampling, and class VIII 9 as the experimental class and VIII 8 as the control class. Research instrumens for measuring mathematical communication skill are questions in the form of essays. The results of the study indicate that the mathematical communication skill of students who study with Problem Based Learning model are better than students what study to use conventional learning in class eight of junior high school 1 Lubuk Alung. Keywords: Mathematics Communication Skill, Problem Based Learning